Pelatihan Bahasa Inggris Berbasis Kontekstual untuk Meningkatkan Kompetensi Komunikasi Calon Pelaku Wisata di Pantai Mananga Aba Sumba Barat Daya - Kartini; Siti Masyitoh; Restisary Nduka; Muhammad Ilham; Muh Nur Udpa (MJI Publisher by PT Mitra Jurnal Indonesia, 2026)
This community service program aimed to improve the English communication competence of prospective tourism actors at Mananga Aba Beach, Southwest Sumba Regency, particularly in speaking skills. The program was initiated in response to the participants’ low English communication abilities, which were indicated by limited vocabulary, lack of speaking fluency, difficulties in pronunciation, and low self-confidence in communicating with foreign tourists. The training employed a contextual teaching and learning approach combined with Task-Based Language Teaching (TBLT) and role-play as the main instructional strategies. The program was conducted over nine meetings consisting of eight instructional sessions and one closing session, involving 25 participants. The training materials were designed progressively and contextually based on tourism-related situations, covering topics such as greetings and introductions, numbers and prices, time, directions and locations, asking for help, tourism attractions, and safety and security. The results demonstrated significant improvement in participants’ speaking abilities, indicated by increased vocabulary mastery, better speaking fluency, improved pronunciation, and greater confidence in communicating without relying on written texts. The contextual, supportive, and non-judgmental learning approach proved effective in creating meaningful learning experiences and encouraging active participation. This program contributed positively to preparing local communities as prospective tourism actors who are better equipped to interact with foreign tourists and support sustainable tourism development at Mananga Aba Beach. Abstrak Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi komunikasi bahasa Inggris calon pelaku wisata di Pantai Mananga Aba, Kabupaten Sumba Barat Daya, khususnya pada keterampilan berbicara (speaking). Program dilatarbelakangi oleh masih rendahnya kemampuan komunikasi bahasa Inggris masyarakat calon pelaku wisata, yang ditunjukkan melalui keterbatasan kosakata, kurangnya kelancaran berbicara, kesulitan pengucapan (pronunciation), serta rendahnya rasa percaya diri dalam berkomunikasi dengan wisatawan asing. Pelatihan dilaksanakan menggunakan pendekatan contextual teaching and learning dengan metode Task-Based Language Teaching (TBLT) dan role-play sebagai strategi utama pembelajaran. Kegiatan dilaksanakan selama sembilan kali pertemuan yang terdiri atas delapan sesi pembelajaran dan satu sesi penutupan, dengan melibatkan 25 peserta. Materi pelatihan dirancang secara bertahap dan aplikatif sesuai konteks kepariwisataan, meliputi greetings and introductions, numbers and prices, time, directions and locations, asking for help, tourism attractions, serta safety and security. Hasil kegiatan menunjukkan adanya peningkatan kemampuan berbicara peserta yang ditandai dengan bertambahnya kosakata, meningkatnya kelancaran berbicara, perbaikan pengucapan, serta meningkatnya rasa percaya diri dalam berkomunikasi tanpa bergantung pada teks tertulis. Pendekatan pembelajaran yang kontekstual, suportif, dan non-judgmental terbukti efektif dalam menciptakan pengalaman belajar yang bermakna dan mendorong partisipasi aktif peserta. Program ini memberikan kontribusi positif dalam mempersiapkan masyarakat lokal sebagai calon pelaku wisata yang lebih siap menghadapi wisatawan asing serta mendukung pengembangan pariwisata berkelanjutan di Pantai Mananga Aba.